Pre-season mental conditioning model for 8-9 year-old tennis players - Iskhak, M. S.; Shilko, V. G. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to theoretically substantiate and test practical benefits of a new pre-season mental conditioning model for the 8-9 year old tennis players.